2018
DOI: 10.3390/medicina54040054
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Tissue HIF-2 Alpha Expression in CIN, N-Acetyl Cysteine, and Sildenafil-Treated Rat Models: An Experimental Study

Abstract: Background and Objectives: Contrast-induced nephropathy (CIN), is acute renal damage due to contrast agents. This study is conducted to evaluate serum and renal heterodimeric nuclear transcription factor (HIF)-2 alpha levels and its tissue expression in contrast-induced nephropathy, and in N-acetyl cysteine (NAC)-and Sildenafil-treated rat models. Materials/Methods: This randomized, controlled, interventional animal study was conducted on Wistar rats. Rats (n = 36) were randomly assigned to four groups: contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Iohexol-induced nephropathy Wistar female rats 50 mg/kg bw, orally Reduced serum and renal tissue levels of HIF-2α and sCr [184].…”
Section: Population Dosage Resultsmentioning
confidence: 99%
“…Iohexol-induced nephropathy Wistar female rats 50 mg/kg bw, orally Reduced serum and renal tissue levels of HIF-2α and sCr [184].…”
Section: Population Dosage Resultsmentioning
confidence: 99%
“…Both sildenafil and tadalafil have been reported to lower sCr levels, demonstrating a positive effect against CIN [ 17 , 21 , 40 , 41 , 42 ]. Evidence from previous studies has indicated that KIM-1 has shown a renoprotective effect mainly in AKI, measured in urine or in renal tissue [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is evidence that CM induces significant histological alterations at the organ/tissue level. Histological alterations include increased organ weight and Bowman space, lobulated glomerulus, alterations of the macula densa region [ 22 ], medullary congestion [ 40 ], inflammatory cell infiltration, intratubular cast formation and obstruction, tubular vacuolization/degeneration-necrosis [ 17 , 41 ], and hemorrhagic changes within the kidney [ 22 ]. Most of the available evidence sources denote an attenuation of the effect of CM following PDE5I administration [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation